Chitobiase, Proteinase, Glycogen and some Trace Elements during Molting Cycle of Mud Crab (Scylla serrata Forskål 1775) - Jintana Salaenoi; Jitlada Bootpugdeethum; Mingkwan Mingmuang; Amara Thongpan (Agriculture and Natural Resources, 2006)
Activity profiles of chitobiase, proteinase and the content of glycogen and trace elements in gill, integument and haemolymph of mud crab (Scylla serrata) during molting cycle were determined. Chitobiase activity was at the highest level of 0.5467±0.0136 μmol min-1mg protein-1 at 1-week premolt (D2) in gill and at 0.1413±0.0026 μmol min-1 mg protein-1 in integument but reached the maximum level of 0.0851±0.0123 μmol min-1mg protein-1 at 24-h postmolt (A2.2) in haemolymph. The high activities of proteinase, on the other hand, were found to be 0.6511 ± 0.0934 units mg protein-1 at 7-day postmolt (B2.3), 0.1553 ± 0.0419 units mg protein-1 at 1-week premolt (D2), and 0.1827±0.0110 units mg protein-1 at 12-h postmolt (A2.1) in gill, integument and haemolymph, respectively. These two enzymes are needed for carapace degradation as well as for chitin synthesis in preparation for carapace formation. For glycogen content, high accumulation of glycogen in the integument was observed throughout the molting cycle except at intermolt (C). In gill, however, the level of glycogen was high only before molting began (D2) while glycogen content in hepatopancreas and muscle, energy reserve tissues, was rather fluctuated but reached the maximum levels at 24-h postmolt (A2.2). As for trace elements, copper, a major component of hemocyanin, was found at high level at intermolt stage (C) in all tissues while magnesium, involving both nerve conduction and muscle contraction, showed the highest content at 7-day postmolt (B2.3) and 1-week premolt (D2) in integument and haemolymph, respectively. On the other hand, zinc showed high content at premolt stage in haemolymph and early postmolt stage in gill supporting its function in calcification. The results confirmed the roles of chitobiase, proteinase, glycogen, and trace elements which corresponded well with molting stages and physiological changes of mud crab.